Determinan Kualitas Hasil Audit Inspektorat Kota Mataram - Khopipah Wandan Sari; Ayudia Sokarina; Lalu Takdir Jumaidi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This study aims to predict the effect of objectivity, integrity, professional skepticism, and spirituality, on the quality of audit results. This research is a research type associative with a kauntitaif approach. The data used is primary data obtained through distributing questionnaires. The sampling technique used was a saturated sample by taking the entire population to be sampled, namely 38 auditors of the Mataram City Inspectorate. The data analysis tool used is Partical Least Square (PLS) version 3.0. The results of this study prove that objectivity, integrity, professional skepticism and spirituality have a positive effect on the quality of the results of the Mataram City Inspectorate. The theoretical implications of this research are as a reinforcement of attribution theory in explaining the role of internal encouragement of auditor behavior (objectivity, integrity, professional skepticism, spirituality) on the quality of audit results.